STUDENTS’ PROBLEMS IN MASTERING SPEAKING SKILL FACED BY THE XI GRADE STUDENTS AT MA INTEGRAL HIDAYATULLAH MANOKWARI - Kartini Kartini; Syahira Syahira (LP4MK STKIP PGRI Lubuklinggau, 2023)
This research aimed to investigate the students’ problem in mastering speaking skills, and the cause of that problem. This research was carried out at MA Integral Hidayatullah Manokwari. This research used qualitative approach with a descriptive analysis method. 28 students of MA Integral Hidayatullah Manokwari were interviewed and fill the questionnaire to determine their experience in speaking class. The result showed that students have lack of vocabulary (96%), Pronunciation 74%, lack of grammar 70%, lack of fluency (96%). Meanwhile, the cause of students’ speaking problems were lack of confidence, fear of making mistake, anxious, shyness, and lack of motivation.